The impact of COVID-19 on GCC equity and debt markets: Evidence from TVP-VAR estimation - Syed, Ali Murad (Frontiers in Applied Mathematics and Statistics, 2022)
COVID-19 has rapidly evolved into a global pandemic and has strongly impacted financial markets of the world, including the Gulf Cooperation Council (GCC) region. Since the outbreak is unprecedented, there is a need to analyze the effects of the disease on volatility spillovers between equity and bond markets. We empirically investigated the impact of the COVID-19 pandemic on the financial equity and debt markets in the GCC region. We used the TVP-VAR dynamic connectedness approach to measure risk transmission in the GCC market. This study investigated the time-varying behavior of GCC equity and conventional and Islamic debt markets using data from 1 January 2019 to 30 August 2021. The results were also validated by performing a DCC-GARCH analysis to check the shock and spillovers among the GCC markets. We found the persistent shock transmitter roles of equity markets to bond and Sukuk markets in the GCC region, and the total dynamic connectedness increased during the first wave of the COVID-19 pandemic. Overall, the significant level of interconnectedness exists within the GCC markets.